2020
DOI: 10.1080/10942912.2020.1751196
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic profiling and antibacterial potential of Saudi Arabian native date palm (Phoenix dactylifera) cultivars

Abstract: Date Palm (Phoenix dactylifera) is one of the important fruit enriched with an impressive list of essential nutrients and a wide range of phenolic compounds with high antibacterial compounds. In order to provide further detailed information on phenolic compounds and antibacterial activities of Date Palm (Phoenix dactylifera), the current study was devoted to investigate and compare three different highly consumable varieties of date palm (Phoenix dactylifera) cultivars, namely Ajwa, Khalas Alkharj, and Al-Qasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Maltose, catechin, myricetin, quercetin, β-sitoserol, digalacturonic acid, chlorogenic acid, and β-carotene were found to be major molecules [ 37 ]. Moreover, the LC-linear ion quadrupole mass spectrometric analysis (LC-MS and LC-MS/MS tandem mass spectrometry) analysis revealed the presence of 3,30-di-O-methyl ellagic acid, 7-methoxyquercetin-O-hexose isomers, caffeic acid, ferulic acid, isomers of quercetin-rutinoside, kaempferol methylether, p-hydroxybenzoic acid, phytol, punicalagin, and quercetin-3-O-glucoside (isoquercitrin) in Ajwa [ 38 ]. The most dominant phenolic compounds in Ajwa dates, according to Hamad et al (2015) [ 39 ], were p-coumaric acid, gallic acid, and ferulic acid derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…Maltose, catechin, myricetin, quercetin, β-sitoserol, digalacturonic acid, chlorogenic acid, and β-carotene were found to be major molecules [ 37 ]. Moreover, the LC-linear ion quadrupole mass spectrometric analysis (LC-MS and LC-MS/MS tandem mass spectrometry) analysis revealed the presence of 3,30-di-O-methyl ellagic acid, 7-methoxyquercetin-O-hexose isomers, caffeic acid, ferulic acid, isomers of quercetin-rutinoside, kaempferol methylether, p-hydroxybenzoic acid, phytol, punicalagin, and quercetin-3-O-glucoside (isoquercitrin) in Ajwa [ 38 ]. The most dominant phenolic compounds in Ajwa dates, according to Hamad et al (2015) [ 39 ], were p-coumaric acid, gallic acid, and ferulic acid derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…The potent activity was related to the active components of S. persica, including flavonoids, salvadorine, alkaloids, cyanogenic, salvadourea, glycosides, and tannins, which are known to possess strong antimicrobial activity [131][132][133]. Methanolic extracts from the leaves, stem, flower, and fruit of Conocarpus erectus L. and the leaves of Aerva javanica exhibited strong antibacterial activity against Bacillus subtilis, S. aureus, and the acid-fast bacterium Mycobacterium phlei [134][135][136]. Furthermore, the methanolic extracts of Mentha × piperita and Mentha longifolia populations grown in northern SA showed that M. × piperita contained the flavonoids naringin 328.8 mg/100 g DW, cynaroside 162.8 mg/100 g DW, and higher phenolic acid content than M. longifolia: rosmarinic acid 1547.6 mg/100 g DW, cryptochlorogenic acid 91.7 mg/100 g DW, and chlorogenic acid 69.4 mg/100 g DW.…”
Section: Antibacterial Activity Of Saudi Arabian Plants and Their Pot...mentioning
confidence: 99%
“…However, a recent study revealed the presence of phenolic compounds in the aerial parts of Wodyetia bifurcata (Sengab et al, 2015). Phenolic compounds exhibit various physiological properties such as antioxidant (Hanula et al, 2020), anti-microbial (Alshwyeh, 2020), anti-inflammatory (Sengab et al, 2015;John and Shahidi, 2019) and anti-cancer (Kim et al, 2010;Palanisamy et al, 2022a) activities.…”
Section: Introductionmentioning
confidence: 99%